Test-retest reliability of level-specific CE-Chirp auditory brainstem response in normal-hearing adults - Jamaludin, Fatin Nabila; Dzulkarnain, Ahmad Aidil Arafat; Shahrudin, Fatin Amira; Marzuki, Muhammad Nasrullah (The Korean Audiological Society and Korean Otological Society, 2021)
Background and Objectives: There is growing interest in the use of the Level-specific (LS) CE-Chirp® stimulus in auditory brainstem response (ABR) due to its ability to produce prominent ABR waves with robust amplitudes. There are no known studies that investigate the test-retest reliability of the ABR to the LS CE-Chirp® stimulus. The present study aims to investigate the test-retest reliability of the ABR to the LS CE-Chirp® stimulus and compare its reliability with the ABR to standard click stimulus at multiple intensity levels in normal-hearing adults. Subjects and Methods: Eleven normal-hearing adults participated. The ABR test was repeated twice in the same clinical session and conducted again in another session. The ABR was acquired using both the click and LS CE-Chirp® stimuli at 4 presentation levels (80, 60, 40, and 20 dBnHL). Only the right ear was tested using the ipsilateral electrode montage. The reliability of the ABR findings (amplitudes and latencies) to the click and LS CE-Chirp®stimuli within the same clinical session and between the two clinical sessions was calculated using an intra-class correlation coefficient analysis (ICC). Results: The results showed a significant correlation of the ABR findings (amplitude and latencies) to both stimuli within the same session and between the clinical sessions. The ICC values ranged from moderate to excellent. Conclusions: The ABR results from both the LS CE-Chirp® and click stimuli were consistent and reliable over the two clinical sessions suggesting that both stimuli can be used for neurological diagnoses with the same reliability.